The incidence of osteoradionecrosis of the jaws in oral cavity cancer patients treated with intensity-modulated radiotherapy: a systematic review and meta-analysis - de Almeida-Silva, Luis Augusto [UNESP]; Lupp, Juliana dos Santos [UNESP]; Sobral-Silva, Leonardo Alvares [UNESP]; dos Santos, Luiz Augusto Rodrigues [UNESP]; Marques, Thays Oliveira [UNESP]; da Silva, Danillo Babinskas Ribeiro [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Bianchi-de-Moraes, Michelle [UNESP] (Elsevier, 2024)
Objective: A systematic review with meta-analysis was conducted to define the incidence of osteoradionecrosis (ORN) in patients with oral cavity cancer (OCC) treated with intensity-modulated radiotherapy (IMRT), and to identify the risk factors influencing its development. Study Design: Six databases were searched systematically. A meta-analysis was performed to determine overall, spontaneous, and dental extraction-attributed incidences of ORN. The Grading of Recommendations Assessment, Development, and Evaluation tool evaluated evidence certainty. Results: Out of 11 eligible studies, 6 underwent meta-analysis for the overall aggregated ORN incidence in OCC patients receiving IMRT, resulting in an incidence rate of 8% (95% CI: 6%-11%). Regarding development reasons, 2 studies were assessed, revealing an incidence of 36% (95% CI: 1%-98%) for spontaneous ORN, and 17% (95% CI: 5%-44%) ensued from dental extraction exclusively pre-RT. All rates had very low certainty of evidence. Factors significantly correlated with ORN development included postoperative RT use (78%), employment of therapeutic doses above 50 Gy, and mandibular involvement (80.5%). Conclusion: The findings suggest that IMRT alone is not sufficient to decrease ORN rates in OCC patients, underscoring the importance of precisely identifying the involved risk factors. However, further detailed primary studies will be necessary.